The History Of Palang Pintu As A Local Cultural Value Became An Icon Of Betawi Traditional Weddings - Handayani, Yeni; Permana, Rahayu; Nurbaity (PT. Hafasy Dwi Nawasena, 2024)
This research aims to examine the history and symbolic meaning of the doorstop as a local cultural value which has become an icon in traditional Betawi weddings. The doorstop is an important element in traditional Betawi wedding ceremonies, which have existed since the 19th century and function as a symbol of unity and agreement between two families. Through a historical and qualitative approach, this research found that doorstops not only act as physical barriers, but also have a deep meaning that reflects the values ​​of family, togetherness, and respect for ancestral traditions. This research also shows that although the basic shape of doorstops remains consistent, there are variations in design and decoration that reflect the changing aesthetics and tastes of modern Betawi society. The research results emphasize the importance of preserving local cultural values ​​such as doorstops in facing the flow of globalization and modernization. A deep understanding of the history and meaning of doorstops can increase public appreciation for Betawi cultural values ​​and encourage conservation measures by the government and cultural organizations. Thus, the doorstop is not only a ritual element in a traditional Betawi wedding, but also a cultural symbol that is rich in meaning and important for maintaining the identity and cultural heritage of the Betawi people. This research highlights the need for concerted efforts in preserving and promoting this tradition so that it remains alive and appreciated by future generations.